Performance Evaluation Of Research Assistants By Copras Method - Arzu Organ; Engin Yalçın (European Scientific Journal, ESJ, 2016)
Performance evaluation of research assistant has become an important factor and a strategic decision for universities. However, this decision is generally complex. Many conflicting criteria should be taken into account at the same time. Correct solution of the problem is related to decision maker’s multiple criterion evaluation in the light of alternatives. In this study, research assistants’ performance evaluation is carried out by COPRAS method. The method of complex proportional assessment (COPRAS) developed by the authors aims at solving this problem. This method assumes direct and proportional dependence of the significance and utility degree of investigated versions on a system of criteria adequately describing the alternatives and on values and weights of the criteria. This study aims to solve performance determination problem of research assistants. A numerical example is given to demonstrate the applicability and effectiveness of the proposed approach. In the end ranking carried out by COPRAS method is given.